Guess a rhyme : peoms to complete! riddles to solve! - Weinberg, Larry (New York : Random House, 1982)
A collection of peoms with final rhyming words omitted , allowing the reader to guess the correct word to complete each poem.
Keywords: American poetry; English language - Rhyme; Literary recreations